2019
DOI: 10.3892/etm.2019.8033
|View full text |Cite
|
Sign up to set email alerts
|

Failure of initial superselective renal arterial embolization in the treatment of renal hemorrhage after percutaneous nephrolithotomy: A respective analysis of risk factors

Abstract: Superselective renal arterial embolization (SRAE) is a well-established method for the treatment of severe hemorrhage following percutaneous nephrolithotomy (PCNL). However, there remains a significant rate of failures requiring repeat SRAE or nephrectomy. To identify risk factors for initial treatment failure of SRAE, the data of patients who had undergone SRAE for severe bleeding due to PCNL between August 2005 and June 2016 were retrospectively analyzed. A total of 98 patients required SRAE for bleeding con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Recently, with the introduction of new interventional devices and embolization materials, embolization technology has been further developed (14). In order to minimize the damage of renal function, superselective renal arterial embolization (SRAE) has been widely performed (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, with the introduction of new interventional devices and embolization materials, embolization technology has been further developed (14). In order to minimize the damage of renal function, superselective renal arterial embolization (SRAE) has been widely performed (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we retrospectively evaluated the safety and efficacy of SRAE in the treatment of hemorrhage after PCNL. In addition, although renal artery embolization has been regarded as the treatment of choice for postoperative bleeding of PCNL (18)(19)(20), there are still reports of recurrent hemorrhage after embolization (1, 7), and even Mao et al reported that up to 17.3% of patients experienced initial treatment failure and underwent repeat SRAE (16). The failure of embolization may be partly due to immature embolization techniques and improper selection of embolization materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it is possible to perform superselective renal arterial embolization (SRAE), which minimizes the loss of renal function. 3 After selective angioembolization, hemoglobin levels should be monitored closely.…”
Section: Discussionmentioning
confidence: 99%
“…Authors opined carefully selecting patients for multitract percutaneous nephrolithotomy, making an extra effort to identify all bleeding vessels during angiography and not using gelatin sponge as the only embolic material could potentially decrease the risk of failure of initial superselective renal arterial embolization after percutaneous nephrolithotomy [13]. Another study identified large tract size, multiple bleeding sites, renal vascular aberration/tortuosity as significant risk factors for increased risk of initial treatment failure of superselective renal arterial embolization [14]. All our patients were successfully managed by initial embolization.…”
Section: Discussionmentioning
confidence: 99%